Bacterial vaginosis testing gaps for transmasculine patients may exacerbate health disparities - Thompson, Hale M.; Rusie, Laura K.; Schneider, John A.; Mehta, Supriya D. (Frontiers in Reproductive Health, 2024)
Bacterial vaginosis (BV) is associated with non-optimal changes in the vaginal microbiome and increased susceptibility to STIs and HIV in cisgender women. Much less is known about the sexual health of transmasculine people and susceptibility to BV, STIs, and HIV. This study's objective was to assess BV testing and outcomes of transmasculine and cisgender women patient populations at a large, LGBTQ+ federally qualified health center. Methods: Retrospective electronic health record data were extracted for eligible patients having at least one primary care visit between January 1, 2021, and December 31, 2021. Transmasculine patients were limited to those with a testosterone prescription in 2021. We conducted log binomial regression analysis to determine the probability of receiving a BV test based on gender identity, adjusting for sociodemographic characteristics. Results: During 2021, 4,903 cisgender women patients and 1,867 transmasculine patients had at least one primary care visit. Compared to cisgender women, transmasculine patients were disproportionately young, White, queer, privately insured, living outside Chicago, and had a lower rate of BV testing (1.9% v. 17.3%, p<0.001). Controlling for sociodemographics, transmasculine patients were less likely to receive a BV test (Prevalence Ratio = 0.19 [95% CI 0.13-0.27]). Discussion: The low rate of BV testing among transmasculine patients may contribute to disparities in reproductive health outcomes. Prospective community-and provider-engaged research is needed to better understand the multifactorial determinants for sexual healthcare and gender-affirming care for transmasculine patients. In particular, the impact of exogenous testosterone on the vaginal microbiome should also be determined.